2010
DOI: 10.1007/s00264-010-1073-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the incidence and progression of radiographic osteoarthritis of the knee among Japanese

Abstract: This longitudinal study aimed to identify risk factors for the incidence and progression of radiographic knee osteoarthritis (OA). We examined the inhabitants of Miyagawa village aged ≥65 years every two years between 1997 and 2007. Anteroposterior radiographs of both knees were graded for OA using the Kellgren-Lawrence (K/L) grading system. Knee OA was defined as grade ≥2. We recorded the incidence of knee OA among participants in whom both knees changed from K/L grades 0 or 1 to ≥2 over a four-year follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 21 publications
3
68
2
4
Order By: Relevance
“…It is interesting, then, to consider that females are well recognised as particularly susceptible to OA [19]. Evidence-based medicine has shown that OA prevalence and incidence are generally higher in females [22,23]. Taken together, these findings suggest that the presence of apelin may contribute to differences in the incidence of OA in males and females.…”
Section: Discussionmentioning
confidence: 86%
“…It is interesting, then, to consider that females are well recognised as particularly susceptible to OA [19]. Evidence-based medicine has shown that OA prevalence and incidence are generally higher in females [22,23]. Taken together, these findings suggest that the presence of apelin may contribute to differences in the incidence of OA in males and females.…”
Section: Discussionmentioning
confidence: 86%
“…10 Female sex, age, and BMI are well-known risk factors for OA, as shown in previous studies. [24][25][26][27][28] Also, in the literature, a low level of education was found to be a significant factor associated with OA. 29,30 Hochman et al 10 compared age, sex, and educational level in knee OA patients between those who used NP descriptors and who did not use NP descriptors.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a multivariate degenerative disease of synovial joints resulting from both mechanical and biological factors, among which sex, age, genetic factors, trauma and obesity play the most important role [1]. The influence of obesity on the development of OA was recognised either in respect to the mechanical load leading to increased feasibility of damage of the joint structures [2], or as a result of activation of mechanoreceptors on cartilage surface, which in turn can lead to the synthesis of the inflammatory mediators [3].…”
Section: Introductionmentioning
confidence: 99%